Soil N transformation and microbial community structure as affected by adding biochar to a paddy soil of subtropical China - Ming LI; Ming LIU; Zhong-pei LI; Chun-yu JIANG; Meng WU (Journal of Integrative Agriculture, 2016)
We have had little understanding on the effects of different types and quantities of biochar amendment on soil N transformation process and the microbial properties. In this study, various biochars were produced from straw residues and wood chips, and then added separately to a paddy soil at rates of 0.5, 1 and 2% (w/w). The effects of biochar application on soil net N mineralization and nitrification processes, chemical and microbial properties were examined in the laboratory experiment. After 135 d of incubation, addition of straw biochars increased soil pH to larger extent than wood biochars. The biochar-amended soils had 37.7, 7.3 and 227.6% more soil organic carbon (SOC), available P and K contents, respectively, than the control soil. The rates of net N mineralization and nitrification increased significantly as biochars quantity rose, and straw biochars had greater effect on N transformation rate than wood biochars. Soil microbial biomass carbon increased by 14.8, 45.5 and 62.5% relative to the control when 0.5, 1 and 2% biochars (both straw- and wood-derived biochars), respectively, were added. Moreover, biochars amendments significantly enhanced the concentrations of phospholipid fatty acids (PLFAs), as the general bacteria abundance increased by 161.0% on average. Multivariate analysis suggested that the three rice straw biochar (RB) application levels induced different changes in soil microbial community structure, but there was no significant difference between RB and masson pine biochar (MB) until the application rate reached 2%. Our results showed that biochars amendment can increase soil nutrient content, affect the N transformation process, and alter soil microbial properties, all of which are biochar type and quantity dependent. Therefore, addition of biochars to soil may be an appropriate way to disposal waste and improve soil quality, while the biochar type and addition rate should be taken into consideration before its large-scale application in agro-ecosystem.